Sensing the quantum limit in scanning tunnelling spectroscopy - Christian R. Ast (Nature Portfolio, 2016)
The tunnelling current in scanning tunnelling spectroscopy has often been treated by a continuous charge flow, which lacks proper treatment of charge quantization. Here, Ast et al. unveil the effects of granularity in the tunnelling current at extremely low temperatures by including P(E) theory, thereby reaching the quantum limit in scanning tunnelling spectroscopy.